Aerospace series. Sleeving, heat-shrinkable, for binding, insulation and identification. Semi-flexible polyvinylidene fluoride (PVDF). Temperature range. 55 °C to 150 °C. Product standard Part 105, (19th September 2019) - British Standards Institution,
No abstract available